Overcoming Challenges of Peer Assessment Implementation in Online Collaborative Learning in Higher Institutions of Learning - Kalema, Job; Katusiime, Jane; Kawuma, Simon; Natumanya, Deborah (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2025)
Online collaborative learning has become an essential component of higher education, offering students opportunities to engage in peer-based learning activities. Peer assessment, as a tool for enhancing collaborative learning, has demonstrated significant potential but also presents several implementation challenges. The primary objectives of this paper are to identify and analyze the key challenges encountered in the implementation of peer assessment within online collaborative learning environments. This study employed a mixed-methods approach, combining qualitative and quantitative research methods to explore the challenges faced in implementing peer assessment in online collaborative learning environments. Approximately 35% of students in our study reported difficulties related to the peer assessment platforms, including usability issues and limited integration with other learning management systems.35% of students in our study found the assessment rubrics unclear or insufficiently detailed. The challenges identified in this study, particularly those concerning technological limitations, lack of training, and issues with fairness and trust, have significant implications for the implementation of peer assessment in online collaborative learning. Based on the results and expert review, it is clear that overcoming these challenges requires a multifaceted approach. Technological, pedagogical, and social challenges all play a role in hindering the effectiveness of peer assessment, but these challenges can be addressed through targeted strategies.